An agnostic assessment of real exchange rate dynamics in LATAM - Carrera, Jorge Eduardo (2016)
This paper investigates the dynamics of multilateral real effective exchange rates (RER) using a panel data set of 19 Latin American countries for the last 45 years. Our results do not support the PPP, so real shocks tend to have permanent effects. Using non-stationary panel econometrics, our estimations show that: a) terms of trade, productivity, capital flows, government spending and net foreign assets exhibit strong relationships with RER; b) exchange rate regimes are not neutral and c) the subsamples regressions are consistent. Finally, we discuss the causes of the persistent overvaluation that the region has experienced in the 2000’s.